2014
DOI: 10.1111/jofo.12081
|View full text |Cite
|
Sign up to set email alerts
|

Demographic trends of Brown Pelicans in Louisiana before and after the Deepwater Horizon oil spill

Abstract: ABSTRACT. Marine oil spills may have extensive and deleterious effects on coastal waterbirds, but pre-spill data sets are often not available for making comparisons of demographics to the period following a spill. The 2010 Deepwater Horizon oil spill allowed us to compare Brown Pelican (Pelecanus occidentalis) demographics during pre-and post-spill years. We banded 1114 pelicans on Louisiana barrier islands from 2007 to 2009, tracked their distribution via band re-sighting surveys from 2008 to 2011, and conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…Using both a carcass sampling model and an exposure probability model, Haney et al (2014b) calculated that approximately 700,000 birds died in the coastal GOM as a result of the Deepwater Horizon oil spill, but the numbers may be as low as 320,000 and as high as 1,900,000 within the 95% uncertainty bounds. Walter et al (2014) and pulmonary consolidation as well as mortality rates higher than previously recorded. A critique and reply followed publication.…”
Section: Authors Noted Occasional Foam Debris Particles Exceededcontrasting
confidence: 53%
“…Using both a carcass sampling model and an exposure probability model, Haney et al (2014b) calculated that approximately 700,000 birds died in the coastal GOM as a result of the Deepwater Horizon oil spill, but the numbers may be as low as 320,000 and as high as 1,900,000 within the 95% uncertainty bounds. Walter et al (2014) and pulmonary consolidation as well as mortality rates higher than previously recorded. A critique and reply followed publication.…”
Section: Authors Noted Occasional Foam Debris Particles Exceededcontrasting
confidence: 53%
“…The study was criticized by Sackmann and Becker (2015) who suggested that an underestimating of carcass transport probability to shorelines was leading to overestimation of bird deaths by an order of magnitude; a comment which was refuted in a response letter from Haney et al (2015). Walter et al (2014) assessed the demographic trends of brown pelicans in LA before and after the DWH spill by banding 1114 individuals on LA barrier islands from 2007 to 2009 and tracking their distribution via band re-sighting surveys from 2008 to 2011. The study found little age-variation within the population that could readily be assigned to spill-related mortality, which was contrary to expectations.…”
Section: Birdsmentioning
confidence: 99%
“…A study of Louisiana colonies over forty years suggested that when conditions at a colony site deteriorate, birds may move en masse to another site [ 82 ]. Several Louisiana colonies are known to have experienced severe physical degradation as a result of the spill [ 30 , 99 ] and persistent exposure to oil and oil-based compounds in subsequent years [ 100 ]. The degradation of high-quality nesting sites could have played a large role in dispersal of individuals from the area, resulting in increased gene flow between some, but not all pairs of populations.…”
Section: Discussionmentioning
confidence: 99%
“…The species has since established new nesting colonies in Louisiana [ 44 ], and its global population has grown to levels sufficient for its removal from the Endangered Species list in 2009 [ 45 ], but the degree to which Louisiana populations may have experienced genetic bottlenecks, particularly those associated with reintroduction, remains unclear. Additionally, the Deepwater Horizon oil spill in the year following delisting had immediate negative impacts on seabird and wading bird populations in the northern Gulf of Mexico, including brown pelicans [ 29 , 30 ]. These impacts include acute and direct mortality, as well as sub-lethal effects on behavior and condition, but as with most taxa the magnitude and nature of spill-related impacts for brown pelicans remain unclear.…”
Section: Introductionmentioning
confidence: 99%